Prediction of suicidal behaviors in hospitalized children and adolescents in middle-income countries: a case study of Brazil - Carvalho, Isis F.; Miranda, Debora; da Silva, Ana Paula Couto; Lacerda, Anisio M.; Meira Jr., Wagner; Romano-Silva, Marco A.; Lobato, Maria Carolina; Pappa, Gisele L. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2023: Anais do XX Encontro Nacional de Inteligência Artificial e Computacional, 2023)
Suicide is the first leading cause of death among children and adolescents worldwide. Predictors of suicide-related behaviours might help in the task of intervening to avoid or monitor future suicide risks. In this paper, a sample of individuals who were taken to a Child Psychiatry Facility in Brazil was analyzed. Machine learning algorithms were used to generate models for predicting suicidal behaviour, and the features that better explain this complex behaviour were also analyzed. Results show a sensitivity of 0.83 and a specificity of 0.97.